2003
DOI: 10.1111/j.1468-3083.2004.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Profound inhibition of chronic itch induced by stimulation of thin cutaneous nerve fibres

Abstract: Background Despite the fact that severe itch is common in many dermatological diseases, the therapeutic arsenal against itching is limited. From neurophysiological experiments, using a new technique termed cutaneous field stimulation, it is known that acute itch can be effectively relieved by stimulation of cutaneous nociceptors. Methods We tested the effects of cutaneous field stimulation (25 min, 16 electrodes, 4 Hz per electrode, up to 0.8 mA) on chronic itch due to atopic dermatitis. Transcutaneous electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Additionally, 74% of patients who had not responded to local steroid treatment showed a significant decline of > 50% in pruritus intensity. Only one previous study has compared the efficacy of TENS versus cutaneous field stimulation on chronic itch and that was in patients with AD chronic itch; it was found in that study that both remedies improved the itch sensation during ongoing stimulation; however, after cessation of cutaneous field stimulation, but not TENS, the itch sensation was significantly depressed for up to 7 h after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 74% of patients who had not responded to local steroid treatment showed a significant decline of > 50% in pruritus intensity. Only one previous study has compared the efficacy of TENS versus cutaneous field stimulation on chronic itch and that was in patients with AD chronic itch; it was found in that study that both remedies improved the itch sensation during ongoing stimulation; however, after cessation of cutaneous field stimulation, but not TENS, the itch sensation was significantly depressed for up to 7 h after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature we used 4 Hz low frequency stimulation over 5 minutes as the conditioning test stimulus [16], [17], and an intermediate 30 Hz frequency as an intended sham frequency [18][21]. We have choosen a 4 Hz stimulation paradigm in order to make it more difficult for the subject to distinguish the 4 Hz (in contrast to 1 Hz) conditioning from an intended sham stimulation of intermediate frequencies (30 Hz in the present study).…”
Section: Methodsmentioning
confidence: 99%
“…Applying this methodology, the study reported that only 2/8 tested subjects reported itch when histamine injections were given in allodynic skin as opposed to normal skin, which is in some accordance with the reduction in itch sensation observed in the present experiment. Similarly, homotopically applied CFS was later shown to be an effectual antipruritic strategy for treatment of itch in atopic dermatitis patients (Nilsson et al, 2004), indicating that prolonged itch-inhibition established by a painful stimuli also affects non-histaminergic itch signalling which is characteristic in atopic dermatitis Papoiu et al, 2011). Given that even mild homotopic painful stimuli are capable of greatly reducing itch (Graham et al, 1951;Yosipovitch et al, 2005Yosipovitch et al, , 2007Kosteletzky et al, 2009;Andersen et al, 2017a), it is hard to evaluate whether the observed itch reduction was related to capsaicin-induced secondary sensitization or simply ongoing counter-stimulation.…”
Section: Decreased Itch In a Capsaicin-evoked Allodynic And Hyperalgementioning
confidence: 99%